Adenosine A2A receptor antagonism protects against hyperoxia‐induced retinal vascular loss via cellular proliferation. Issue 9 (21st August 2021) - Zhong, Ding‐Juan; Zhang, Yu; Zhang, Shuya; Ge, Yuan‐Yuan; Tong, Mengyun; Feng, Yijia; You, Feng; Zhao, Xinyue; Wang, Ke; Zhang, Liping; Liu, Xiaoling; Chen, Jiang‐Fan
Abstract: Retinopathy of prematurity (ROP) remains one of the major causes of blindness in children worldwide. While current ROP treatments are mostly disruptive to reduce proliferative neovascularization by targeting the hypoxic phase, protection against early hyperoxia‐induced retinal vascular loss represents an effective therapeutic window, but no such therapeutic strategy is available. Built upon our recent demonstration that the protection against oxygen‐induced retinopathy by adenosine A2A receptor (A2A R) antagonists is most effective when administered at the hyperoxia (not hypoxic) phase, we here uncovered the cellular mechanism underlying the A2A R‐mediated protection against early hyperoxia‐induced retinal vascular loss by reversing the inhibition of cellular proliferation via possibly multiple signaling pathways. Specifically, we revealed two distinct stages of the hyperoxia phase with greater cellular proliferation and apoptosis activities and upregulation of adenosine signaling at postnatal 9 day (P9) but reduced cellular activities and adenosine‐A2A R signaling at P12. Importantly, the A2A R‐mediated protection at P9 was associated with the reversal of hyperoxia‐induced inhibition of progenitor cells at the peripheral retina at P9 and of retinal endothelial proliferation at P9 and P12. The critical role of cellular proliferation in the hyperoxia‐induced retinal vascular loss was validated by the increased avascular areas by siRNA knockdown of the multiple signaling molecules involved in modulation of cellular proliferation, including activin receptor‐like kinase 1, DNA‐binding protein inhibitor 1, and vascular endothelial growth factor‐A.